Overview of Communist Countries, Comparative Ethical Tendencies and Islamic Religious Education - Nurhuda, Hasan; Tafsir, Ahmad; Nurrohman, H. (Lembaga Yasin AlSys, 2023)
Throughout this chapter, my aim has been to emphasize different aspects of two distinct perspectives. The first perspective belongs to a researcher who recollects his past as a student in a communist country, and interprets his life experiences through the lens of his impact on his education and teaching profession. The second perspective is that of a researcher who looks to the future, despite limited resources, with a desire to connect with global research in his area of interest: educational ethics. Our research in the field of educational ethics draws inspiration and support from international studies such as philosophical works, moral psychology, and resources from sociology, organizational psychology, and pedagogy. As for expected trends in comparative and international education, I have divided them into three categories:: The trends in comparative education research can be categorized into three main themes: the application of a comparative lens to various educational themes such as history, philosophy, curriculum, sociology, politics, and psychology; the integration of quantitative and qualitative methodologies to support research; and the potential impact of global models on inspiring local initiatives that cannot be replicated.